( x − 1 ) ( x + 3 ) ( x − 4 ) ( x − 8 ) + m
If the expression above is a perfect square polynomial, then what is m ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We form two pairs out of the given terms which are multiplied:
( x − 1 ) ( x − 4 ) and ( x − 8 ) ( x + 3 ) Notice that, on expanding the expression becomes
( x 2 − 5 x + 4 ) ( x 2 − 5 x − 2 4 ) + m
Let x 2 − 5 x = t
⇒ ( t + 4 ) ( t − 2 4 ) + m = k 2
t 2 − 2 0 t − 9 6 + m = k 2
Notice that t 2 − 2 0 t + 1 0 0 = ( t − 1 0 ) 2
⇒ x = 1 9 6
Note: This solution is specific to this problem only.
How about setting x=0 and checking the options!!
Log in to reply
You could use that approach for an exam, but if you do such a thing at a subjective exam, you get a zero. That's why I gave a proper solution instead of setting x=0.
( x − 1 ) ( x + 3 ) ( x − 4 ) ( x − 8 ) + m May use Vieta’s formulas to expand. = x 4 − 1 0 x 3 + 5 x 2 + 1 0 0 x − 9 6 + m Divided by x 2 . = x 2 − 1 0 x + 5 + x 1 0 0 + x 2 m − 9 6 = ( x 2 − 2 m − 9 6 + x 2 m − 9 6 ) − 1 0 ( x − x 1 0 ) + 5 + 2 m − 9 6 = ( x − x m − 9 6 ) 2 − 1 0 ( x − x 1 0 ) + 5 + 2 m − 9 6 Equating m − 9 6 = 1 0 ⟹ m = 1 9 6 = ( x − x 1 0 ) 2 − 2 ( 5 ) ( x − x 1 0 ) + 2 5 = ( x − x 1 0 − 5 ) 2 A perfect square.
⟹ m = 1 9 6 .
This is not a solution. Kindly delete this, or reply to this comment with a valid explanation.
I don't know if it is a good way to solve, but the constant terms multiply to − 9 6 and from adding the options only 1 9 6 gives a perfect square with a + sign.
Problem Loading...
Note Loading...
Set Loading...
Nice Problem Deepansh! ( x − 1 ) ( x + 3 ) ( x − 4 ) ( x − 8 ) = ( x 2 − 5 x + 4 ) ( x 2 − 5 x − 2 4 ) .
Then Let ( x 2 − 5 x − 2 4 ) = y .
The rest polynomial becomes y + 2 8 .
Now we can write this as
y ( y + 2 8 ) = y 2 + 2 8 y .
Now we know to be a square the factors must be equal or we should be able to factorise the above as ( x + a ) ( x + a ) .
The above condition is fulfilled only when The last term is 196.
Then we can factorise it as ( y 2 + 2 8 y + 1 9 6 ) = ( y + 1 4 ) ( y + 1 4 ) . Hence we get our solution!